Mathematical model of the impact of chemotherapy and antiangiogenic therapy on drug resistance in glioma growth - Hanum Latifah; Susyanto Nanang; Ertiningsih Dwi (Computational and Mathematical Biophysics)
This study presents a mathematical model of glioma growth dynamics with drug resistance, capturing interactions among five cell populations – glial cells, sensitive and resistant glioma cells, endothelial cells, and neurons – alongside chemotherapy and antiangiogenic therapy. Glioma, a malignant tumor originating in glial cells, undergoes chemotherapy-induced mutations, leading to drug-resistant variants that affect both tumor and normal cells. The model incorporates a Holling Type II response function to optimize treatment doses while inducing angiogenic dormancy. Stability analysis identifies three equilibrium points – two stable and one unstable – while numerical simulations using phase portraits and trajectory diagrams illustrate the impact of combined therapies. This model provides insights into glioma progression and drug resistance, emphasizing the efficacy of combined therapies for optimizing treatment strategies.